Fabrication of Self‐Oscillating Micelles with a Built‐In Oxidizing Agent. Issue 10 (29th January 2020) - Yoshizawa, Toshiki; Onoda, Michika; Ueki, Takeshi; Tamate, Ryota; Akimoto, Aya Mizutani; Yoshida, Ryo
Abstract: Various biological behaviors are fueled by "respiration", which is an example of catabolism. So far, we have reported various self‐oscillating soft materials exhibiting bioinspired dynamic movements. These autonomous polymer systems are driven by the Belousov–Zhabotinsky (BZ) reaction, which is analogous to the tricarboxylic acid (TCA) cycle that is an integral part of respiration. However, in the BZ reaction, the external addition of an oxidizing agent is necessary to initiate the oxidation process, which is realized by intracellular moieties such as ubiquinone in living systems. Herein, we realized self‐oscillating micelles that are driven without the external addition of an oxidizing agent. This was achieved by embedding the oxidizing source into the structure of the self‐oscillating AB diblock copolymers. This strategy introduces a new function equivalent to intracellular oxidizing moieties, and is useful for the design of completely autonomous bioinspired materials. Abstract : Bioinspired and autonomous : Self‐oscillating micelles with a built‐in oxidant source equivalent to an intracellular oxidizing species exhibit structural oscillation between unimers and micelles without the exterior addition of an oxidizing agent.